Kejut Tanam Cara Pindah Cabutan pada Pembibitan Kelapa Sawit - Sudirman Yahya; Awilham Manurung (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2002)
To find out the possibility of long distance transplanting from the pre to main nursery of oil palm, a research had been conducted to study the effect of bare-root (soiless) and delayed transplanting on seedling growth. The research was a two factor factorial experiment, seedling age of 2 and 3 months, and 5 level transplanting times: conventional (direct planting), bare-root and delayed-transplanting for 1, 3, 5, and 7 days. The experiment was arranged in a randomized complete design. The results indicated that 95 - 100% of the seedlings with bare root and delayed transplanting were successfully survive and continuous to grow. Two month old seedlings were able to overcome the transplanting shock better than three month old seedlings. The seedling of bare-roots and delayed- planting for up to 7 days, still performed a normal growth and there was no significant difference among time of delayed-plantings. The seedlings of delayed transplanting grew two weeks later than the conventional transplanting Key words: Transplanting shock, Bare-root method, Delayed planting.